Outcome of pediatric advanced Hodgkin lymphoma treated with ABVD and predictors of inferior survival: a multicenter study of 186 patients. Issue 7 (3rd July 2017) - Bhethanabhotla, Sainath; Jain, Sandeep; Kapoor, Gauri; Mahajan, Amita; Chopra, Anita; Vishnubhatla, Sreenivas; Bakhshi, Sameer
Abstract: Clinical stage alone is used for risk stratification in treatment of pediatric advanced Hodgkin lymphoma (HL). To identify other risk factors, we collected data from three tertiary centers on 186 patients with advanced stage (IIB–IV) consecutively treated with Adriamycin, bleomycin, vinblastine, Dacarbazine (ABVD) chemotherapy ± radiotherapy. Freedom from treatment failure (FFTF) and overall survival (OS) were end points. With median follow-up period of 57.9 months (range: 1–151 months), five-year FFTF and OS was 84.8% (95% CI 78.6–89.3%) and 95.3% (95% CI 90.78–97.6%), respectively. We identified stage-4 [HR-3.6(1.25, 9.97); p  = .017], high total leukocyte count (>15, 000/mm 3 ) [HR-2.6(1.3, 8.1); p  = .008] and lymphopenia (lymphocyte count ≤8%) [HR-4.9(1.7, 14.1); p  = .002] predictive of inferior FFTF. Patients with none or one of these risk factors had significantly better five-year FFTF (91.9%) as compared to those with risk factors (two risk factor [74.7%; p  = .001]; 3, 4 risk factors [14.3%; p  < .0001]). Patients without these risk factors can be treated with ABVD and may not need intensive therapy.